2019
DOI: 10.21776/ub.jtsl.2019.006.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemberian Kompos Bunker Diperkaya Dengan Limbah Cair Pabrik Kelapa Sawit Pada Pertumbuhan Bibit Kelapa Sawit Di Bibitan Utama

Abstract: Provision of Compost Bunkers enriched with palm oil mill effluent Aims to determine the treatment of types of compost and the treatment of NPK fertilizer doses on the provision of compost Bunkers are enriched with palm oil mill effluent on the growth of oil palm seedlings The use of compost in the main nursery is one of the most important ingredients applied in growing media. This study was carried out in the Bangun Bandar garden of PT. Socfindo, Serdang Bedagai district, Dolok Masihul sub-district with a alti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…As a result, carbon, and nitrogen in the compost decreased and increased respectively. The principle of composting was to reduce the C/N ratio of an organic compound to reach the C/N ratio of the soil (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The maturity indicator of compost was based on the value of the C/N ratio around 10-20 [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, carbon, and nitrogen in the compost decreased and increased respectively. The principle of composting was to reduce the C/N ratio of an organic compound to reach the C/N ratio of the soil (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The maturity indicator of compost was based on the value of the C/N ratio around 10-20 [17].…”
Section: Resultsmentioning
confidence: 99%
“…Eggshell can A Method of Determining the C/N Ratio from Aerobically Treated Brem Compost Waste be used as a bioactivator which consists of 98.2% CaCO3 [10]. The high content of calcium in the eggshell was potent to use as fertilizer and as an ingredient to neutralize the acidity of a fertilizer [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the source of additive used, previous study reported the potency of tofu dregs waste to be utilized as fertilizer due to its rich protein content [15]. Other study also emphasized various nutrient content found in tofu dregs waste, including fat, crude fiber, calcium, phosphorus, and magnesium [16].…”
Section: Plant Growthmentioning
confidence: 99%
“…But statistically, the treatment of compost with various comparisons of POME 1: 1.3, 1: 1.9 and 1: 2.6 can increase the total N content of the soil with very high criteria, the more volume of POME given in the composting process the more the total N content increases. This is in line with the results of compost quality enriched by various POME comparisons, where the more volume of POME used the higher the nutrient content of C-organic, N, P, K and Mg. [15] The treatment of NPK fertilizer dosage has a very significant effect on plant tuber diameter, canopy wet weight and canopy dry weight that is 25-50% the NPK fertilizer dose. and According to POME is rich in organic compounds and carbon dioxide.…”
Section: Table 2 Growth Of Oil Palm Seedlings By Providing Compost Types With Various Comparison Of Pome Notementioning
confidence: 99%
“…Showed that the composting method used the Bunker system, the ratio between the yield of empty bunches to POME was 1: 5 producing compost with the highest nutrient / nutrient content of Nitrogen, Phosphorus and Potassium over a period of 25 days [14]. The treatment of compost significantly affected plant height, plant tuber diameter, canopy wet weight, canopy dry weight and root canopy ratio was 25% POME [15].. Utilization of compost in the main nurseries is one of the most important materials applied in the nursery media.…”
Section: Introductionmentioning
confidence: 99%